A catered St. Patrick's Day : a mystery with recipes - Crawford, Isis (Crawford, Isis. Mystery with recipes., 2012)
When Mike Sweeney is found floating in a vat of green beer and the nephew of one of their best customers is accused of the crime, Bernie and Libby Simmons, the owners of A Little Taste of Heaven, must find the real killer.